THE IMPORTANCE OF AEROSPACE INSTRUMENTS IN THE RESEARCH OF EARTH TYPES (American Journal of Technology and Applied Sciences, 2023)
Aerospace instruments are critical tools of great importance in the study of the Earth's crust. These devices are used to collect information about the earth's atmosphere, oceans, horizons, strange areas and many others. These devices are used for space flight, earth tracking and other quality data acquisition. The study of land categories helps to study the world's climate changes, atmospheric hardness, natural resources and many other important information. This abstract discusses in detail the importance of spacecraft in the study of the Earth's crust.